Generalised impossible differentials of advanced encryption standard - Phan, R.C.W.; Siddiqi, M.U. (2001)
A class of generalised four-round impossible differentials of the advanced encryption standard is presented and shown to be the best that can be obtained with the miss-in-the-middle technique